Portal Vein Blessure - Pittamiglio, Horacio; Perrone, Luis; Pereyra Borrelli, César; Lyonnet, Alberto (Cirugía del Uruguay, 1983)
... Two patients with portal vein blessure treated by direct vein surgical repair a·re presented. Bibliogra phy shows low fre q u ency and extreme gravity. Different surgical procedures are analyzed. Concluding that the elective procedure is direct venous repair by suture or patch.